Is Perceived Athlete Leadership Quality Related to Inside Sacrifice and Perceived Performance in Team Sports? The Mediating Role of Team Identification - López-Gajardo, Miguel A.; Pulido, Juan J.; Tapia-Serrano, Miguel A.; Ramírez-Bravo, Iván; Leo, Francisco M. (Frontiers in Psychology, 2021)
The study aimed to analyze the relationship between athletes’ perceptions of athlete leadership quality, team identification, inside sacrifice, and performance. A total of 299 players from collective sports (soccer, beach soccer, basketball, volleyball; Mage 19.05, SD = 5.10) participated through a cross-sectional survey design. Data were analyzed using structural equation modelling. Results highlight the positive relationships between athlete leadership quality and inside sacrifice and perceived performance, and between inside sacrifice and perceived performance. Furthermore, inside sacrifice perceived by the athletes was a positive mediator between athlete leadership quality and perceived performance. Also, team identification was a positive mediator in the association between inside sacrifice and perceived performance. These findings extend knowledge about the athlete leadership quality context. These results can be also useful for further research and implications in team sports’ performance, as coaches and sports psychologists would have more information about the perceptions of their teams’ leader quality to achieve positive outcomes in players’ inside sacrifice and performance. The findings also highlight the importance of developing team identification to improve the relationships between athlete leadership quality, inside sacrifice, and perceived performance.